Efektifitas Pelayanan Publik di Sub Bidang Instalasi Patologi Klinik RSUD Dr. Soetomo, Surabaya - Andika, Dimas Bayu; Santoso, Teguh; Sukarno, Sukarno (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
The initial findings, researchers found that part of the Administration in the field of installation of clinical pathology Hospitals Dr. Sutomo Surabaya less nimble in providing service to the public as patients. This makes the family the patient should wait longer. On the other hand, patients are also waiting for certainty when it served for want of knowing about the diagnosis of the disease. When these conditions continuously happen, then many patients abandoned and waiting on the clarity of the given service. The purpose of this research was conducted to find out and describe the effectiveness of the service in the field of installation of clinical pathology Hospitals Dr. Sutomo Surabaya. Data analysis was done with a qualitative descriptive data analysis techniques. The results showed that the effectiveness of the service in the field of installation of clinical pathology Hospitals Dr. Sutomo Surabaya can be seen from a few things. The first time factor, showed that based on the SOP, the waiting time of the overall service is 140 minutes ranging from registration to results accepted. It is also influenced by the level of service as there are kegawatan CITO or urgency. Second, the intricate factors shows that employees in the field of installation of clinical pathology Hospitals Dr. Sutomo Surabaya works in accordance with the existing procedures and SOPS. the third factor is the style of service giver showed that the attitude shown by the employees of the Sub fields of installation of clinical pathology Hospitals Dr. Sutomo Surabaya to patients is good and friendly attitude. But in practice, the parties still found the Sub Field installation of clinical pathology Hospitals Dr. Sutomo Surabaya less fair in giving service to the patients. This is because the party Sub Field installation of clinical pathology Hospitals Dr. Sutomo Surabaya regarded giving priority to services in patients who have a familial relationship with the officials of the Sub fields of installation of clinical pathology Hospitals Dr. Sutomo Surabaya. broadly speaking, the effectiveness of the service in the field of installation of clinical pathology Hospitals Dr. Sutomo Surabaya insufficient because there are still constraints in service and complaints that are perceived by the patient.Keywords: Effectiveness, Stewardship, Public Service